Bone Defects in Tibia Managed by the Bifocal vs. Trifocal Bone Transport Technique: A Retrospective Comparative Study - Abulaiti, Alimujiang; Liu, Yanshi; Cai, Feiyu; Liu, Kai; Abula, Abulaiti; Maimaiti, Xiayimaierdan; Ren, Peng; Yusufu, Aihemaitijiang (Frontiers in Surgery, 2022)
Background: The purpose of this study was to evaluate the clinical effectiveness and determine the differences, if any, between trifocal and bifocal bone transport technique in the reconstruction of long segmental tibial bone defects caused by infection using a monolateral rail external fixator. Methods: A total of 53 consecutive patients with long segmental tibial bone defects caused by infection and treated by monolateral rail external fixator in our department were retrospectively collected and analyzed from January 2013 to April 2019, including 39 males and 14 females with an average age of 38.8±12.4 years (range 19 to 65 years). 32 patients were treated by bifocal bone transport (BFT) technique, and the other 21 patients were managed by trifocal bone transport (TFT) technique. The demographic data, operation duration, docking time, external fixation time, and external fixation index were documented and analyzed. Difficulties that occur during the treatment were classified according to Paley. The clinical outcomes were evaluated by the Association for the Study and Application of the Method of Ilizarov criteria (ASAMI) at the last clinical visit. Results: All patients achieved an infection-free union finally, and there was no significant difference between the two groups in demographic data and both ASAMI bone and functional scores (P>0.05). The mean defect size and operation duration in TFT (9.4±1.5 cm, 161.9±8.9 minutes) were larger than that in BFT (7.8±1.8 cm, 122.5±11.2 minutes) (P<0.05). The mean docking time, external fixation time, and external fixation index in TFT (65.9±10.8 days, 328.0±57.2 days, 34.8±2.1 days/cm) were all less than those in BFT (96.8±22.6 days, 474.5±103.2 days, 60.8±1.9 days/cm) (P<0.05). Difficulties and complications were more prevalent in the BFT group, while less in the TFT group (P<0.05). Conclusion: Both the trifocal and bifocal bone transport technique in the reconstruction of long segmental tibial bone defects caused by infection using a monolateral rail external fixator achieve satisfactory clinical outcomes. The trifocal bone transport technique can significantly decrease the docking time, external fixation time, external fixation index, difficulties, and complications compared with the bifocal bone transport technique.